Integrated landslide susceptibility zonation and ecological risk assessment in Koraput District, Eastern India: a multivariate approach - Tanmoy Chatterjee; Janmejay Sethy; Pratap Kottapalli; Puspita Hazra; Biswajit Ghosh; Amitarani Ray; Duryadhan Behera; Shreerup Goswami; Surajit Munshi (Journal of Sedimentary Environments, 2026)

Influence of nisin on water activity, textural and other quality attributes of paneer (Indian cottage cheese) during storage - Chandrakanta Sen; Pinaki Ranjan Ray; Shamim Hossain; Mahasweta Bhattacharyya; Surajit Mondal; Anindita Debnath (Food and Humanity, 2023)

Geochemical evolution of dissolved trace elements in space and time in the Ramganga River, India - Indra Sekhar Sen; Sarwar Nizam; Aqib Ansari; Michael Bowes; Bharat Choudhary; Miriam Glendell; Surajit Ray; Marian Scott; Claire Miller; Craig Wilkie; Rajiv Sinha (Environmental Monitoring and Assessment, 2023)
Understanding the spatiotemporal dynamics of river water chemistry from its source to sinks is critical for constraining the origin, transformation, and “hotspots” of contaminants in a river basin. To provide new spatiotemporal constraints on river chemistry, dissolved trace element concentrations were measured at 17 targeted locations across the Ramganga River catchment. River water samples were collected across three seasons: pre-monsoon, monsoon, and post-monsoon between 2019 and 2021. To remove the dependency of trace element concentrations on discharge, we used molar ratios, as discharge data on Indian transboundary rivers are not publicly available. The dataset reveals significant spatiotemporal variability in dissolved trace element concentrations of the Ramganga River. Samples collected upstream of Moradabad, a major industrial city in western Uttar Pradesh, are characterized by ~ 1.2–2.5 times higher average concentrations of most of the trace elements except Sc, V, Cr, Rb, and Pb, likely due to intense water–rock interactions in the headwaters. Such kind of enrichment in trace metal concentrations was also observed at sites downstream of large cities and industrial centers. However, such enrichment was not enough to bring a major change in the River Ganga chemistry, as the signals got diluted downstream of the Ramganga-Ganga confluence. The average river water composition of the Ramganga River was comparable to worldwide river water composition, albeit a few sites were characterized by very high concentrations of dissolved trace elements. Finally, we provide an outlook that calls for an assessment of stable non-traditional isotopes that are ideally suited to track the origin and transformation of elements such as Li, Mg, Ca, Ti, V, Cr, Fe, Ni, Cu, Zn, Sr, Ag, Cd, Sn, Pt, and Hg in Indian rivers.

Getting the most out of maths: How to coordinate mathematical modelling research to support a pandemic, lessons learnt from three initiatives that were part of the COVID-19 response in the UK - Ciara E. Dangerfield; I. David Abrahams; Chris Budd; Matt Butchers; Michael E. Cates; Alan R. Champneys; Christine S.M. Currie; Jessica Enright; Julia R. Gog; Alain Goriely; T. Déirdre Hollingsworth; Rebecca B. Hoyle; et al. (Journal of Theoretical Biology, 2023)

Analyzing surface air temperature and rainfall in univariate framework, quantifying uncertainty through Shannon entropy and prediction through artificial neural network - Samayita Nag Ray; Surajit Chattopadhyay (Earth Science Informatics, 2021)

A Markov chain approach to the predictability of surface temperature over the northeastern part of India - Samayita Nag Ray; Sanghita Bose; Surajit Chattopadhyay (Theoretical and Applied Climatology, 2021)

Combination of all-trans retinoic acid and taxol regressed glioblastoma T98G xenografts in nude mice - Surajit Karmakar; Naren L. Banik; Sunil J. Patel; Swapan K. Ray (Apoptosis, 2007)

Garlic compounds induced calpain and intrinsic caspase cascade for apoptosis in human malignant neuroblastoma SH-SY5Y cells - Surajit Karmakar; Naren L. Banik; Sunil J. Patel; Swapan K. Ray (Apoptosis, 2007)